Strategi Pelibatan Generasi Muda Dalam Pengelolaan Pariwisata Di Desa Tenganan Pegringsingan, Kecamatan Manggis, Kabupaten Karangasem - Putra, Putu Guntur Pramana; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i02.p05, 2018)
The research aims to find out tourism potential and what strategy for involving young generation in managing tourism at the village of Tenganan Pegringsingan. The research was located at the village of Tenganan Pegringsingan. The scope of research was reinterpretation, Think Global and Act Locally, institutionalization, and institutional, type of data being used was qualitative data, source of data being used was primary and secondary data. Data sampling method being used was observation, interview and documentation study. Informant determination in this qualitative study was using Purposive Sampling. Data analysis being used was descriptive qualitative. The first to be done was conducting observation to social phenomenon, and then conducting categorization toward obtained information, next was explaining categorization, and then explaining the relation of categorization and drew general conclusions . Based on the result obtained, natural potential possessed by the village of Tenganan consists of vast rice fields, suitable to be used as trekking path across rice fields, and green forest which has been managed as ecotourism and existing trekking path. Existing cultural potential among others was, such as “Nyakan Suci, Neduh, Mekare-kare, Muhu-muhu, Mesanggah Gedebong, Mesanggah Bongkot, Munjung, Metruna Nyoman, Maling-malingan” and other traditions. This cultural potential becomes the attraction for tourists to visit the village of Tenganan. T he strategy for involving young generation which including role reinterpretation attempted through internal and external of young generation. Next the slogan of Think Global and Act Locally, through global thinking and acting locally, and institutionalization covering tourism spirit of young generation, spirit to mastering internet in developing tourism network and spirit to carry forward the tradition of the ancestors. Next is institutional which including the strengthening of organization based on culture namely Sekaha Truna and Deha. The extension of Sekeha Truna Truni based on the necessity, based on Tourism Management such as Sekaha Truna and Truni. So, the role of young generation in tourism management is very important for regeneration of tourism management at the village of  Tenganan in the future.   Keywords : The younge generation, The involving strategy, Managing tourism, Tenganan Pegringsingan Village